2020
DOI: 10.1111/jcal.12505
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry‐based mobile learning in secondary school science education: A systematic review

Abstract: Recent years have seen a growing call for inquiry-based learning in science education, and mobile technologies are perceived as increasingly valuable tools to support this approach. However, there is a lack of understanding of mobile technology-supported inquiry-based learning (mIBL) in secondary science education. More evidence-based, nuanced insights are needed into how using mobile technologies might facilitate students' engagement with various levels of inquiry and enhance their science learning. We, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 65 publications
(141 reference statements)
1
41
0
4
Order By: Relevance
“…Nevertheless, some studies have illustrated the benefits of using mobile technology-integrated instruction, such as the affordance of authentic learning activities, inquiry learning experience, timely learning guidance and enhancement of students' engagement, learning and higher order thinking skills (C. H. Chen, 2020;Li & Wong, 2020). Furthermore, several review studies on mobile technology-integrated instruction have found that the major part of the papers addressed issues of te system designs for mobile learning or students' learning effectiveness (e.g., Hwang & Fu, 2020;Liu et al, 2021). Thus, few studies have investigated teachers' conceptions of teaching in the context of mobile technology-integrated instruction.…”
Section: Trends and Gaps In Mobile Technology-integrated Instructionmentioning
confidence: 99%
“…Nevertheless, some studies have illustrated the benefits of using mobile technology-integrated instruction, such as the affordance of authentic learning activities, inquiry learning experience, timely learning guidance and enhancement of students' engagement, learning and higher order thinking skills (C. H. Chen, 2020;Li & Wong, 2020). Furthermore, several review studies on mobile technology-integrated instruction have found that the major part of the papers addressed issues of te system designs for mobile learning or students' learning effectiveness (e.g., Hwang & Fu, 2020;Liu et al, 2021). Thus, few studies have investigated teachers' conceptions of teaching in the context of mobile technology-integrated instruction.…”
Section: Trends and Gaps In Mobile Technology-integrated Instructionmentioning
confidence: 99%
“…In addition, it was found that whereas the Orientation, Conceptualization, Investigation, and Conclusion phases focus mainly on the problem to be solved by the inquiry approach, the Discussion phase goes beyond that, leading the learners more towards the analysis of the inquiry process, not only to its outcomes. Therefore, the Discussion phase is especially valuable in acquiring inquiry skills through reflection on the process (see Liu et al, 2021 for a review of studies focusing on collaborative inquiry).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In spite of the wide use of the inquiry-based learning process as a learning approach (see Archer-Kuhn, Lee, Hewson, & Burns, 2020;Liu, Zowghi, Kearney, & Bano, 2021;Misra, 2020), few studies have focused on the assessment of the outcomes of the inquiry process. Both inquiry skills and knowledge acquired through inquiry could be regarded as outcomes of the inquiry process.…”
Section: Introductionmentioning
confidence: 99%
“…In systematic reviews of trends in mobile learning research, its potential to aid in education is shown (e.g., Bano et al, 2018;Diacopoulos & Crompton, 2020;Lai, 2019;Liu et al, 2021;Yildiz et al, 2020), as well as its main challenges (Benali & Ally, 2020). In Crompton and Burke (2020), it was reported that 46% of the time mobile devices are used to replicate activities that can be performed without technology.…”
Section: Introductionmentioning
confidence: 99%